“Uma constelação de culpas” : arquétipos narrativos dos nazistas no Julgamento de Nuremberg (1945-1946) - Maria Visconti Sales (2023)
The Nuremberg Trials, which took place between 1945 and 1946, represent a significant milestone in the denazification process in Europe after World War II. With a tribunal composed of the Allied countries and war winners as judges and prosecutors, this debut trial brought twenty-one Nazis to the dock. Considered the most outstanding representatives of the Third Reich, these men used the courtroom as a stage to offer a final consideration of the Nazi regime and their role in this dark period of German history. The thesis aims to identify and interpret, based on the analysis of the narratives of nineteen Nazis during the proceedings, the different ways that the defendants spoke about themselves at the Nuremberg Trials, transforming these speeches into archetypes. The sources used for this analysis are the transcripts of the Nuremberg Trials and the interviews that the Nazis gave to the psychiatrist Leon Goldensohn and the psychologist Gustave Gilbert during the trial period. The narratives were selected considering only the defendants who testified during the trial. The starting point of the research was to understand that, although all Nazis were fighting against the death penalty, it is possible to recognize patterns and narrative strategies that are repeated throughout this trial and come from different men with different government positions and who faced different accusations – consequently, they also had different sentences. Some Nazis continued to defend the National Socialist ideology until the end. Others denied involvement or knowledge of the regime’s crimes and presented themselves as unimportant individuals within the structure of the Third Reich. It was also possible to identify Nazis who claimed to have deeply regretted their actions; men who said they were great resisters, despite their positions in the regime; military personnel who justified themselves by the need to obey orders; and diplomats who advocated for a non-extremist conservatism. By identifying discursive patterns and transforming them into typologies, it is possible to apply the archetypes developed in this thesis in subsequent analyzes of other denazification courts. The main argument of this work is, in this sense and above all, a proposal for creating a methodological analysis tool.